PENGARUH DESAIN INTERIOR KAFE DI KOTA MEDAN TERHADAP PERILAKU PENGUNJUNG PADA MASA NEW NORMAL - Vivian, Clarissa; Darmayanti, Tessa Eka (Aksen : Journal of Design and Creative Industry, 2022)
COVID-19 was declared a pandemic in 2020 because of its high transmission rate. The Community Activities Restrictions Enforcement, a policy that was made to inhibit the transmission of the virus then caused a slowdown in the economic sector. Indonesia’s Economic Recovery from the COVID-19 pandemic was carried out by implementing the New Normal policy, and new habits while maintaining health protocols. Social life is also re-opened, including cafes that have started to operate again as a place to socialize. Strict health protocols must be implemented in cafes to break the chain of COVID-19 transmission. The purpose of this study was to find out how the post-pandemic cafe interior design influences COVID-19 health protocol compliance. This research uses qualitative methods with literature studies and direct observation by visiting 3 cafes in the city of Medan that have implemented the new normal system. The cafes that will be visited are Pilastro Cafe which is located at Jalan H. Misbah No. 18B, Elixir Coffee Roastery at Jalan Waringin No.13, and Five Lines of Coffee at Jalan Dewa Ruci No. 3. This study provides information to readers, especially designers, regarding visitor responses to café’s interior design with the health protocols implementation which can be used as a reference for designing future projects. Keywords: Café, interior, new normal